2020
DOI: 10.3892/ol.2020.12054
|View full text |Cite
|
Sign up to set email alerts
|

A novel definition of microvessel density in renal cell carcinoma: Angiogenesis plus vasculogenic mimicry

Abstract: The present study proposed the novel concept of total microvessel density (TMVD), which is the combination of the MVD and the vasculogenic mimicry (VM) status, and evaluated its clinical significance in patients with renal cell carcinoma (RCC). For that purpose, tumor samples from 183 patients with primary RCC were examined by CD34 single or periodic acid Schiff (PAS)/CD34 dual histology staining. MVD and VM were determined according to previous literature. Clinical information (tumor stage and grade, and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
(96 reference statements)
1
14
0
Order By: Relevance
“…CD34/PAS double staining is a method commonly used to verify the formation of VM in tumor tissue 26 . Briefly, after immunohistochemical staining for CD34 (Abcam, 1:100 dilution) was completed, sections were stained with periodic acid solution for 10 minutes, then rinsed twice with distilled water for 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD34/PAS double staining is a method commonly used to verify the formation of VM in tumor tissue 26 . Briefly, after immunohistochemical staining for CD34 (Abcam, 1:100 dilution) was completed, sections were stained with periodic acid solution for 10 minutes, then rinsed twice with distilled water for 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…CD34/PAS double staining is a method commonly used to verify the formation of VM in tumor tissue. 26 Briefly, after immunohistochemical staining for CD34 (Abcam, 1:100 dilution) was completed, sections were stained with periodic acid solution for 10 minutes, then rinsed twice with distilled water for 3 minutes. Then schiff solution was applied to the sections for 20 minutes prior to rinsing with distilled water, counterstaining with hematoxylin, and dehydrating with ethanol gradient.…”
Section: Methodsmentioning
confidence: 99%
“…This condition induces the initialization of the VEGF cascade [9], ending in neoangiogenesis. A new definition of microvessel density in CCRCC has been recently published [22]. These authors consider the sum of classical microvessel density and vasculogenic mimicry as the total microvessel density and correlate this sum with prognosis [22].…”
Section: Microenvironmental Contextmentioning
confidence: 99%
“…A new definition of microvessel density in CCRCC has been recently published [22]. These authors consider the sum of classical microvessel density and vasculogenic mimicry as the total microvessel density and correlate this sum with prognosis [22]. Since these neoplasms are highly vascularized, the antiangiogenic tyrosine-kinase inhibitors have had a relevant role in the therapeutic armamentarium, particularly in metastatic patients [23].…”
Section: Microenvironmental Contextmentioning
confidence: 99%
“…Metronomic Chemotherapy to Target Endothelial, Cancer, and Cancer Stem Cells A systematic review of preclinical studies has confirmed the significant relationship between reduced tumor vascularization and inhibition of tumor development, thus highlighting the importance of vascular efficiency [76]. However, a microvascular density analysis cannot distinguish between angiogenic and non-angiogenic tumors, therefore the histopathological growth pattern of tumors must be taken into account [77] or the term "microvessel density" redefined [78,79]. Two tumor phenotypes have been distinguised in murine tumor models and tumor specimens from patients based on the vascular/stromal architecture ratio, which are known as "tumor vessel" and "stromal vessel" and are sensitive or refractory to the VEGFR-2-blocking antibody DC101, respectively [80].…”
Section: Cellular Components Of Thementioning
confidence: 99%